Pengaruh suasana toko dan kemudahan pada niat pembelian ulang di coffee shop - Septasari Cahya Nazhifah,; Widyastuti, (Jurnal Ilmu Manajemen, 2025)
This study aims to examine the influence of store atmosphere and convenience on repurchase intention at coffee shops. As coffee shops have become a popular destination for young professionals to work, study, and socialize, understanding factors that encourage repeat visits is crucial for business sustainability. A quantitative method with an explanatory research design was employed. Data were collected from 97 respondents who had visited Tomoro Coffee at least twice in the last three months. Using purposive sampling, the study applied multiple linear regression analysis through SPSS version 25. The findings reveal that both store atmosphere and convenience significantly affect repurchase intention. A pleasant and well-designed store atmosphere, including lighting and seating arrangement, contributes to a positive customer experience. Convenience, such as ease of ordering, accessibility, and efficient service, also plays a key role in encouraging repeat purchases. The model explains 67.9% of the variation in repurchase intention. The implications of this study suggest that coffee shops should continue improving its store environment and service convenience. Special attention should be given to aspects with low customer ratings, such as background music and complaint handling. Future research may consider including other influencing variables like price, lifestyle, and service quality to enrich the understanding of customer loyalty in the coffee shop industry.